Understanding Students’ Digital Literacy as Part of Their Personal Information Management Skills - Hariyanto, Annisha Wichita Putri; Perdani, Nur’aini; Heriyanto, Heriyanto (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
In the contemporary digital age, the concept of privacy assumes heightened significance. Nevertheless, the phenomenon of disclosing personal information online has led to an increase in cybercrime cases that pose a threat to the privacy of internet users, including those who utilize social media platforms such as Instagram. The objective of this study is to ascertain the extent to which there is a correlation between digital literacy skills and the management of personal information on Instagram among the undergraduate students at Diponegoro University's School of Library Science. This study employed the simple random sampling technique to determine the sample. We collected data by distributing questionnaires using Google Forms, resulting in 170 data points. We then subjected the data to analysis using Pearson's correlation technique, the product moment. Furthermore, the correlation coefficient value was obtained as r = 0.462, with a significance value of <0.001, thus satisfying the criterion of p < 0.05. The results indicate a significant positive correlation between digital literacy skills and the ability to manage personal information on Instagram. College students with higher digital literacy skills are more adept at managing their personal information on social media Instagram, reducing the risk of cybercrime.
Keywords: personal information management; digital library; instagram; undergraduate studens